Administration of testosterone improves the prothrombotic and antifibrinolytic parameters associated with its deficiency in an orchidectiomized rat model. (4th July 2019) - Alqahtani, Sultan A.; Alhawiti, Naif M.
Abstract: This study investigated the effect of testosterone deficiency and replacement on platelets function and aggregation, coagulation, and fibrinolysis in young adult healthy male rats. Rats were classified into three groups ( n  = 6/group) of either "a sham-operated+ vehicle, " "an orchidectomized (ORX)+ vehicle, " and "an ORX+testosterone propionate (0.5 mg/kg, 3X/week, S.C)." All treatments were carried out for 12 weeks. Our results showed that ORX rats had induced platelets aggregation and coagulation and inhibited fibrinolysis. ORX-induced rats had increased ratios of adenosine diphosphate-induced aggregation, shorter bleeding time, clotting time, prothrombin time, and activated partial thromboplastin time and their sera showed increased levels of thromboxane B2 and fibrinogen levels. Concomitantly, their plasma showed increased TPA-1 and decreased tissue plasminogen activator (tPA) levels. At molecular levels, the aorta of ORX-induced rats showed increased aortic mRNA and protein levels of plasminogen activator inhibitor-1 (PAI-1), protein levels of von Willebrand Factor (vWF) and decreased mRNA and protein levels of tPA, and their liver showed increased protein levels of prothrombin and factor VII. Testosterone post-therapy to ORX-induced rats significantly reversed all these hematological and molecular changes. In conclusion, independent of any other risk factors, testosterone deficiency induces platelets aggregation and hypercoagulation and inhibits fibrinolysis, effects that can be reversed by testosterone therapy.